The broken the Paradox and the Potential of India's one Billion Ladder (Haryana Random house, 2017)
This book presents a ground-up view of emergent realities, delving into the lives of ordinary individuals. through decades long investigations, while living in villages and slum communities, he reveals the eye opening details of missed opportunities and the immense untapped talent that can be honed to enable tremendous consequences for growth and equity.
Keywords: Dollar economy and Rupee economy -- Economic development -- Social conditions -- Indian Villages and Development -- Urban Area -- Poverty Prevention -- Information and Experience -- Democracy -- Economic Growth and Development -- individual Development